2015
DOI: 10.1093/carcin/bgv040
|View full text |Cite
|
Sign up to set email alerts
|

A novel prostate cancer therapeutic strategy using icaritin-activated arylhydrocarbon-receptor to co-target androgen receptor and its splice variants

Abstract: Persistent androgen receptor (AR) signaling is the key driving force behind progression and development of castration-resistant prostate cancer (CRPC). In many patients, AR COOH-terminal truncated splice variants (ARvs) play a critical role in contributing to the resistance against androgen depletion therapy. Unfortunately, clinically used antiandrogens like bicalutamide (BIC) and enzalutamide (MDV), which target the ligand binding domain, have failed to suppress these AR variants. Here, we report for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…A natural prenylflavonoid, also known as icaritin (ICT), inhibited AR-regulated genes in AR-positive prostate cancer cells via AR-depended pathways. 23) All these studies suggested the role of AR in metastatic prostate cancer. Thus, we manipulated cellular AR level and examined wheth- er AR overexpression abrogates anti-PCa activity of ART.…”
Section: Discussionmentioning
confidence: 98%
“…A natural prenylflavonoid, also known as icaritin (ICT), inhibited AR-regulated genes in AR-positive prostate cancer cells via AR-depended pathways. 23) All these studies suggested the role of AR in metastatic prostate cancer. Thus, we manipulated cellular AR level and examined wheth- er AR overexpression abrogates anti-PCa activity of ART.…”
Section: Discussionmentioning
confidence: 98%
“…Would co-suppressing the two pathways lead to a more robust induction of AR-Vs and AR-V-driven tumor progression? If so, would co-targeting the Akt pathway with an agent that can induce AR-V degradation (Cao, et al 2013; Kwegyir-Afful, et al 2015; Li, et al 2012a; Liu, et al 2014a; Sun, et al 2015; Yamashita, et al 2012; Yu, et al 2014; Zengerling, et al 2012) alleviate this problem? These questions need to be carefully addressed.…”
Section: Ar-v7 Degradationmentioning
confidence: 99%
“…Various approaches have been explored to disrupt AR-V signaling, such as targeting AR N-terminal domain (Myung, et al 2013) or DNA-binding interface (Dalal, et al 2014; Li, et al 2014a), inducing AR-V protein degradation (Cao et al 2013; Kwegyir-Afful et al 2015; Li et al 2012a; Liu et al 2014a; Sun et al 2015; Yamashita et al 2012; Yu et al 2014; Zengerling et al 2012), reducing AR-V expression (Mashima, et al 2010; Zhan, et al 2013), inhibiting AR-V chromatin binding (Chan et al 2015; Li, et al 2015a), disrupting AR-FL and AR-V dimerization (Streicher, et al 2014), or using antisense oligonucleotides against exons shared by AR-FL and AR-Vs (Yamamoto et al 2015). Here, we describe several AR-V-targeting agents that have entered clinical trials for cancer treatment.…”
Section: Therapeutic Targeting Of Ar-vsmentioning
confidence: 99%
“…AR-V1 and AR-V9 were found to be mainly cytoplasmic and were described to be conditionally active, rather than constitutively active, as they exhibited ligand-independent activity in some cell lines but not in others [81,82]. AR-V7 and AR v567es , however, are constitutively active and consistently exhibit nuclear localization in an androgenindependent manner [77,83]. Of these 2 splice variants, more work has been performed analyzing the role of AR-V7 compared with that of AR v567es since it has been possible to develop a variant-specific antibody and complementary sequences, which target the AR-V7 variant.…”
Section: Ar Splice Variantsmentioning
confidence: 99%
“…This work needs further validation in clinical trials, but appears promising in an era of enzalutamide and abiraterone-resistant CRPC. Other AR splice-variant inhibitors are currently in development [83].…”
Section: Ar Splice Variantsmentioning
confidence: 99%